2023
DOI: 10.1590/1516-3180.2021.0852.13062022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound techniques for the detection of developmental dysplasia of the hip: a systematic review and meta-analysis

Abstract: BACKGROUND: Developmental dysplasia of the hip (DDH) encompasses a broad spectrum of hip pathologies, including femoral or acetabular dysplasia, hip instability, or both. According to the medical literature, ultrasonography is the most reliable diagnostic method for DDH. Several techniques for the assessment of hips in newborns and infants, using ultrasonography, have been described. OBJECTIVE: To compare the accuracy of the Graf technique and other diagnostic techniques for DDH. DESIGN AND SETTING: A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
3
0
1
Order By: Relevance
“…In a systematic review of DDH conducted by Harper et al [35], the four studies that compared universal ultrasound screening (for all newborns) and selective ultrasound screening concluded that, in the United Kingdom, the former would be more cost-effective than the latter because it would reduce the rates of late detection and surgery. Similar conclusions have been drawn from studies conducted in countries such as Germany, Austria, and Switzerland [33], suggesting that DDH screening in Brazil should be carried out by using the Graf's method in the entire neonatal population. The economic impact of screening programs is multifactorial and requires careful consideration on the part of governments.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In a systematic review of DDH conducted by Harper et al [35], the four studies that compared universal ultrasound screening (for all newborns) and selective ultrasound screening concluded that, in the United Kingdom, the former would be more cost-effective than the latter because it would reduce the rates of late detection and surgery. Similar conclusions have been drawn from studies conducted in countries such as Germany, Austria, and Switzerland [33], suggesting that DDH screening in Brazil should be carried out by using the Graf's method in the entire neonatal population. The economic impact of screening programs is multifactorial and requires careful consideration on the part of governments.…”
Section: Discussionsupporting
confidence: 73%
“…Walter et al [12] carried out a review of 131 studies from 25 countries to assess whether the objective quality criteria established for the Graf's method were met and concluded that only 68 (51.9%) of those studies presented ultrasound images that were considered to have met Graf's criteria. It is noteworthy that in Germany, Austria, and Switzerland, hip ultrasound can be performed only with a special license obtained by completing a course with instructors certified and authorized by Professor Graf or one of his representatives [33].…”
Section: Challenges Of Physician Training In Ddh Care In Brazilmentioning
confidence: 99%
“…Graf method is the most widely used ultrasound static technique for neonatal hip assessment (2,11). It requires standardised imaging and has been accepted by health systems of several European countries.…”
Section: Discussionmentioning
confidence: 99%
“…2 O ultrassom é um método de imagem confiável para o diagnóstico de DDQ no período neonatal, dentre as vantagens neste tipo de exame: é um procedimento não invasivo e não utiliza radiação ionizante, como desvantagem: é um método operador-dependente. 5 A ultrassonografia para acompanhamento de pacientes com DDQ é feita geralmente até os seis meses de idade. No método ultrassonográfico de Graf é possível avaliar imagens estáticas e dinâmicas e identificar a anatomia do acetábulo, a posição da cabeça do fêmur e a maturação e estabilidade da articulação coxofemoral.…”
Section: Discussionunclassified